Systematic Determination of The Ultrastructure of Local Faba Bean (Vicia faba L.) Seeds Using Light and Scanning Electron Microscopes - Nihat Yılmaz; Handan Şapcı Selamoğlu; Zeynep Arı; Hatice Bekci (Turkish Journal of Agriculture: Food Science and Technology)
The present study was conducted to determine the seed morphologies and macromorphological characteristics of fifteen local faba bean (Vicia faba L.) genotypes collected from different region of Northern Cyprus. The characteristics in the seeds were evaluated using a light microscope (LM) and scanning electron microscope (SEM). SEM pictures were taken of the whole seed and its details. The scope of the research was examined comparatively using LM and SEM, and the seed shapes, surface ornamentation, and quantitative measurements were determined. Different characteristics for seed size and surface were found among the local faba beans accessions. Seed dimensions were between 12.44 and 24.26 mm long and between 9.49 and 17.45 mm wide, colors ranged from yellowish-brown to dark brown, and ornamentation of the seed coat varied. The local faba bean seeds were of subprolate and prolate types. We believe that using this technique to determine the differences among the seeds of different genotypes may play a role in helping to create different programs that can choose specific genotypes to improve cultivars based on the seed characteristics.